Low density lipoprotein delays clearance of triglyceride-rich lipoprotein by human subcutaneous adipose tissue - Simon Bissonnette; Huda Salem; Hanny Wassef; Nathalie Saint-Pierre; Annie Tardif; Alexis Baass; Robert Dufour; May Faraj (Journal of Lipid Research, 2013)
Delayed clearance of triglyceride-rich lipoprotein (TRL) by white adipose tissue (WAT) promotes hypertriglyceridemia and elevated apoB-lipoproteins, which are primarily in the form of LDL. This study examines whether LDL promotes delayed clearance of TRL by WAT. Following the ingestion of a 13C-triolein-labeled high-fat meal, obese women with high plasma apoB (> median 0.93 g/l, N = 11, > 98% as IDL/LDL) had delayed clearance of postprandial 13C-triglyceride and 13C-NEFA over 6 h compared with controls. AUC6 h of plasma 13C-triglyceride and 13C-NEFA correlated with plasma apoB but not with LDL diameter or adipocyte area. There was no group difference in 13C-triolein oxidation rate, which suggests lower 13C-NEFA storage in peripheral tissue in women with high apoB. Ex vivo/in vitro plasma apoB correlated negatively with WAT 3H-lipid following a 4 h incubation of women舗s WAT with synthetic 3H-triolein-TRL. LDL-differentiated 3T3-L1 adipocytes had lower 3H-TRL hydrolysis and 3H-NEFA storage. Treatment of women舗s WAT with their own LDL decreased 3H-TRL hydrolysis and 3H-NEFA uptake. Finally, LDL, although not an LPL substrate, reduced LPL-mediated 3H-TRL hydrolysis as did VLDL and HDL. Exposure to LDL decreases TRL clearance by human WAT ex vivo. This may promote production of apoB-lipoproteins and hypertriglyceridemia through a positive-feedback mechanism in vivo.